2014
DOI: 10.1002/ange.201311235
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Incorporation of Two Different Metal Ions into Programmed Sites in a Duplex by DNA Polymerase Catalyzed Primer Extension

Abstract: Metal-mediated base pairs formed by the coordination of metal ions to natural or artificial bases impart unique chemical and physical properties to nucleic acids and have attracted considerable interest in the field of nanodevices. Ag I ions were found to mediate DNA polymerase catalyzed primer extension through the formation of a C-Ag I -T base pair, as well as the previously reported C-Ag I -A base pair. The comparative susceptibility of dNTPs to Ag I -mediated enzymatic incorporation into the site opposite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In 2004, Ono and co-workers discovered that Hg 2+ is able to coordinate with thymine nucleobases [ 9 12 ]. This discovery has sparked a wave of novel Hg 2+ detection methods, such as oligonucleotide-based luminescence [ 13 28 ], colorimetric [ 29 40 ], electrochemical [ 41 , 42 ] and surface-enhanced Raman scattering methods [ 43 46 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2004, Ono and co-workers discovered that Hg 2+ is able to coordinate with thymine nucleobases [ 9 12 ]. This discovery has sparked a wave of novel Hg 2+ detection methods, such as oligonucleotide-based luminescence [ 13 28 ], colorimetric [ 29 40 ], electrochemical [ 41 , 42 ] and surface-enhanced Raman scattering methods [ 43 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…This discovery has sparked a wave of novel Hg 2+ detection methods, such as oligonucleotide-based luminescence [ 13 28 ], colorimetric [ 29 40 ], electrochemical [ 41 , 42 ] and surface-enhanced Raman scattering methods [ 43 46 ]. Later on, they reported the crystal structure of a DNA duplex containing the T−Hg II −T mismatch, which showed that the T−Hg II −T bond largely distorts DNA structure and also stabilizes B-form DNA [ 12 ]. Moreover, C−Ag I −A [ 47 ] and C−Ag I −T mismatches have also been reported [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[25] silver-mediated base pairs of dC with dA or dT was in the same range as that of the dC-Ag + -dC pair.A lso, successful DNA polymerase-catalyzed primer extension mediated by silver ions by the formation of dC-Ag + pairs with dA, dT,o rd C has been reported. [37] According to the findings on silver ion binding in homochiral DNA duplexesa nd the observation of metal-mediated base pairing in parallel DNA, [38] we anticipated that heterochiral DNA formed by complementary a-d/b-d strandsw ould be capable of forming silver-mediated base pairs when containing mismatches. Consequently,t he formation of silver-mediated base pairs involving a-dC opposite dC, dT,d A, and a-dC (b strand)w as investigated in heterochiral duplexes.…”
mentioning
confidence: 99%
“…However, a few years later, PEX studies performed on this system revealed that a C-Ag I -C base pair could not be formed. 49,50 Scheme 2. PCR amplification using a C-C mismatch A) in the absence of Ag I cations and B) in the presence of Ag I cations.…”
Section: C-ag I -C Base Pairmentioning
confidence: 99%